Hegemoni dalam Naskah Drama 5 Babak Atas Nama Cinta Karya Agus R. Sarjono: Perspektif Antonio Gramsci - Agik Nur Efendi; Septia Rizqi Nur Abni; Erika Kurniawati (Balai Bahasa Kalimantan Tengah, 2022)
This research discusses the issue of state issues in the drama script Atas Nama Cinta by Agus R. Sarjono. The phenomenon of sarcasm or criticism of the social problems that occurred in Indonesia has implied output written in the drama script is relevant to be studied using the sociology of literature. The concept of Antonio Gramsci's Hegemony includes culture, hegemony, common sense, intellectuals, and state in accordance with the drama Atas Nama Cinta. This research uses a qualitative approach. The results of this study indicate that the state is the final form and container of the emergence of conflict. But from the conflicts, the demonstrations, the problem is full of a form of content from the state. The drama script that is said to be